2002
DOI: 10.1111/j.1553-2712.2002.tb01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Delaying Fluid Resuscitation on an Injury to the Systemic Arterial Vasculature

Abstract: Rates of hemorrhage from an arterial injury are related to changes in mean arterial pressure. In this animal model, early aggressive fluid resuscitation in penetrating thoracic trauma exacerbates total hemorrhage volume. Despite resumption of hemorrhage from the site of injury, delaying fluid resuscitation results in the best hemodynamic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…20 Furthermore, studies have shown that the resuscitation rate affects the hemorrhage rate before hemostasis has been achieved. 21,22 It is plausible that blunt and penetrating mechanisms of injury differ because of different hemorrhage rates yielding different physiologic and immunologic responses. In addition, the tissue injury associated with each mechanism of injury is likely different, with less secondary injury usually associated with lowenergy penetrating weapons.…”
Section: Figmentioning
confidence: 99%
“…20 Furthermore, studies have shown that the resuscitation rate affects the hemorrhage rate before hemostasis has been achieved. 21,22 It is plausible that blunt and penetrating mechanisms of injury differ because of different hemorrhage rates yielding different physiologic and immunologic responses. In addition, the tissue injury associated with each mechanism of injury is likely different, with less secondary injury usually associated with lowenergy penetrating weapons.…”
Section: Figmentioning
confidence: 99%
“…(Table 1) This likely suggests a degree of auto resuscitation or mild dilution taking place during the hemorrhagic shock period which may have been amplified by continuous maintenance of hypotensive blood pressure by selective blood draws and normal saline titration [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Some models used to test hemostatic dressings include fluid administration to achieve a target arterial pressure which may require the infusion of large volumes of crystalloid [7,9,11,12]. Although somewhat controversial, high-volume or high-flow infusions after a vascular injury tend to increase both blood loss and mortality, whereas delayed or minimal resuscitation results in less blood loss and improved survival in some models [13][14][15]. We chose to avoid this issue by giving relatively small volumes of fluid.…”
Section: Discussionmentioning
confidence: 97%